2021
DOI: 10.3390/vaccines9020119
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccine Acceptance among Health Care Workers in the United States

Abstract: Background: Acceptance of the COVID-19 vaccine will play a major role in combating the pandemic. Healthcare workers (HCWs) are among the first group to receive vaccination, so it is important to consider their attitudes about COVID-19 vaccination to better address barriers to widespread vaccination acceptance. Methods: We conducted a cross sectional study to assess the attitude of HCWs toward COVID-19 vaccination. Data were collected between 7 October and 9 November 2020. We received 4080 responses out of whic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

97
530
27
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 530 publications
(720 citation statements)
references
References 25 publications
97
530
27
8
Order By: Relevance
“…31,39 Surveys of health care workers reported more hesitancy (than the public) at the beginning of the pandemic, but as the results from clinical trials were released, hesitancy diminished precipitously. 40,41…”
Section: Discussionmentioning
confidence: 99%
“…31,39 Surveys of health care workers reported more hesitancy (than the public) at the beginning of the pandemic, but as the results from clinical trials were released, hesitancy diminished precipitously. 40,41…”
Section: Discussionmentioning
confidence: 99%
“…Other studies by French and French-speaking health professionals in Belgium and Canada found that 75% of French, 76% of Belgian, and 70% of Canadian HCWs want to get vaccinated for COVID-19 [6]. Vaccine acceptance studies in a group of healthcare professionals in the United States showed that 36% of HCWs were willing to get vaccinated as soon as possible, while 56% were not convinced to get vaccinated and wanted to wait to learn more about vaccination [5]. In contrast, in a study conducted in the Democratic Republic of Congo, only 27.7% of respondents expressed a willingness to get vaccinated for COVID-19 [9].…”
Section: Discussionmentioning
confidence: 99%
“…Although the COVID-19 vaccination program can significantly alleviate the problems associated with the spread of the disease, there are still many people who are skeptical about the vaccine, and despite its availability, refuse to take it. Most doubts are raised based on the fact that the vaccine was developed in a very short period of time, and its long-term effects and effectiveness remain unknown [5,6]. The WHO classified "vaccine hesitation" as one of the top 10 health threats in the world last year.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a study also revealed that 28% of healthcare workers in Democratic Republic of Congo are willing to take the COVID-19 vaccine [26]. A study among healthcare workers in the United States revealed that only one in three said they would take the vaccine immediately it becomes available [25]. More so, in Malta, only half of the participants (healthcare workers) stated that they intend to take the COVID-19 vaccine [27].…”
Section: Discussionmentioning
confidence: 99%
“…Our study present insights regarding the willingness of healthcare professional in the EMRO region. Healthcare workers are among the priority group to receive vaccination, so it is important to understand their willingness to take COVID-19 vaccine or not [25]. This will better provide insights to address barriers to widespread COVID-19 vaccination acceptance.…”
Section: Discussionmentioning
confidence: 99%